Case Report: Reconstruction of the Right Atrium With the Left Atrial Appendage - Jiang, Xuan; Liu, Jinduo; Zhang, Yuhai; Gu, Tianxiang; Liu, Bo (Frontiers in Cardiovascular Medicine, 2021)
Abstract: We herein present a case of infective endocarditis of the mitral valve and a paravalvular abscess around the tricuspid valve. Preoperative blood culture confirmed the presence of pathogenic diphtheroids. During the operation, an unexpected infection of the free wall of the right atrium (RA) near the tricuspid annulus was found. We harvested the left atrial appendage (LAA) en bloc. After resection of the infected and abnormal tissues, the resected LAA was used to reconstruct the RA. The infected mitral valve was replaced with a mechanical valve without any accident. Postoperative echocardiography showed that the RA had a supple shape, with no kinking.